The association between applicant gender and racial or ethnic identity and success in the admissions process at a Canadian medical school: a prospective cohort study - Jalil, Rabiya; Nkemdirim, Makela; Roach, Pamela; Panaccione, Remo; Ruzycki, Shannon M (Canadian Medical Education Journal, 2024)
Background: Canadian data suggests that Black candidates may be less successful than other groups when applying to medical school. We sought to comprehensively describe the racial and/or ethnic identity, gender identity, sexual orientation, and ability of applicants to a single Canadian medical school. We also examined for an association between success at each application stage and applicant gender and racial identity. Methods: Class of 2024 applicants to a single Canadian medical school were invited to complete a demographics survey. The odds of achieving each application stage (offered an interview, offered a position, and matriculating) were determined for each demographic group. Results: There were 595 participants (32.4% response rate). The demographics of the applicant pool and matriculating class were similar. There was no difference in interview offers or matriculation between BIPOC and white candidates. Cisgender men were overrepresented in interviews compared to cisgender women (OR 0.64; 95%CI 0.43-0.95; p = 0.03) but not in matriculation. BIPOC cisgender women received more interview invitations compared to other groups (OR 2.74, 95%CI 1.20-6.25; p = 0.02). Conclusions: Differences in applicant success for differing demographic groups were most pronounced being offered an interview.